High Energy Storage Density in Nd(Zn2/3Nb1/3)O3‐Doped BiFeO3–BaTiO3 Ceramics - Wen‐Yi Li; Di Zhou; Da Li; Yan Guo; Wei‐Chen Zhao; Li‐Xia Pang; Shi‐Kuan Sun (Advanced Electronic Materials, 2023)
Abstract Lead‐free ceramics with high recoverable energy density (Wrec) and energy storage efficiency (η) are attractive for advanced pulsed power capacitors to enable greater miniaturization and integration. In this work, a series of perovskite structured (1‐x)(Bi0.6Ba0.4)(Fe0.6Ti0.4)O3−xNd(Zn2/3Nb1/3)O3 (BF‐BT‐NZN) ceramics with high energy storage density through the solid‐state reaction method are successfully prepared, and the breakdown strength (Eb) and energy storage density are further improved by a membrane rolling process. The highest energy densities of the 0.94(BF‐BT)−0.06NZN ceramics are Wrec ≈ 5.6 J cm−3 and η ≈ 82.9%, which are due to the enhanced breakdown field intensity (BDS ≈ 400 kV cm−1) and the maximum polarization (Pmax≈ 38 µC cm−2). These results indicate that (1−x)(Bi0.6Ba0.4) (Fe0.6Ti0.4)O3−xNd(Zn2/3Nb1/3)O3 ceramics are high‐efficiency lead‐free materials for potential application in high‐energy‐storage capacitors.